Overexpression of cytoglobin gene inhibits hypoxic injury to SH-SY5Y neuroblastoma cells - Yu, Xiuling (Medknow Publications & Media Pvt Ltd, 2013)
A plasmid for cytoglobin expression, pAcGFP1-C1-cytoglobin, was transfected into SH-SY5Y cells. Cobalt chloride was used to establish a model of hypoxia. Western blotting indicated that cytoglobin was overexpressed and there was low expression of hypoxia-inducible factor-1α in SH-SY5Y cells after transfection. Following cobalt chloride-induced hypoxia, cytoglobin and hypoxia-inducible factor-1α expression gradually increased in SH-SY5Y cells. Flow cytometry showed that with increasing duration of hypoxia, the proportion of normal cells significantly diminished in the transfected and non-transfected groups. The proportion of cells in the early stages of apoptosis increased. However, the proportion of apoptotic cells was significantly lower in the transfected group compared with the non-transfected group. These results demonstrate that cytoglobin and hypoxia-inducible factor-1α are strongly up-regulated by hypoxia, and that there is a strong relationship between hypoxia-inducible factor-1α and cytoglobin during hypoxic injury.